The Anterior Portion of the Bilateral Temporal Lobes Participates in Music Perception: A Positron Emission Tomography Study - Satoh, Masayuki (AJNR Am J Neuroradiol, 2003)
BACKGROUND AND PURPOSE: The mechanism underlying the perception of music has been the subject of study for many years. We investigated the role of the anterior portion of the temporal lobes in the perception of music in nonmusicians by use of positron emission tomography (PET). METHODS: We used the subtraction technique for PET to investigate the role of the anterior portion of the bilateral temporal lobes in music perception. Nonmusicians performed two kinds of musical tasks: harmony listening and soprano part listening. RESULTS: During the harmony-listening task, the anterior portion of the temporal lobes, cingulate gyri, and cerebellum were bilaterally activated. During the soprano part–listening task, the bilateral superior parietal lobules, and the right precuneus were significantly activated. CONCLUSION: The anterior portion of the bilateral temporal lobes is vital in the discrimination of melodies and chords. Differences between activated brain regions exist between musicians and nonmusicians when listening to a particular vocal part of a musical phrase.